تقدير نموذج إحصائي للتنبؤ بمخاطر الفشل المالي للمؤسسات بواسطة التحليل اللوجستي دراسة تطبيقية على عينة من المؤسسات خلال الفترة (2009-2014) - الحاج, خليفــــــــة; تراري مجـــاوي, حسيـــن (University of Eloued جامعة الوادي, 2017)
تهدف هذه الدراسة إلى بناء نموذج إحصائي للتنبؤ بمخاطر فشل المؤسسات باستخدام التحليل اللوجستي، حيث أُجريت الدراسة على 52 مؤسسة صغيرة ومتوسطة (22 مؤسسة سليمة) و(30 مؤسسة فاشلة) خلال الفترة الممتدة من 2009 إلى 2014، كما تم الاعتماد على بطارية متكونة من 25 نسبة مالية، وخلصت الدراسة إلى انتقاء خمس (05) نسب مالية مدرجة في الدالة الإحصائية اللوجستية: (هيكل التمويل، المردودية الاقتصادية، الاستثمارات، الاستدانة قصيرة الأجل، مؤشر الحجم)، ثبت أن لها قدرة التنبؤ بالمخاطر المالية للمؤسسات الصغيرة والمتوسطة؛ وبلغت نسبة الدقة التنبؤية لهذا النموذج %90. Abstract: This study aimed at building a statistic model in ordre to predict the entreprise’s failure risk using a logistic analysis. It has been applied on 52 small and medium enterprises which 22 are successful and 30 are faulty. It was during the period of 2009 to 2014. This work ends up with the selection of 5 financial ratios (from 25) included in the statistic and logistic function: financing structure, economic profitability, investment, short-term debt, and size index. Thus, it is proven to have a high financial risk predicting capacity whose accuracy rate attains 90%.
Estimating a statistical model to forecast the risk of financial failure of enterprise’s through logistic analysis. A case study of a sample of some enterprises during the period from 2009 to 2014
مجلة رؤى المجلد السابع العدد 12
Keywords: تحليل لوجستي، نسب مالية، مؤسسات فاشلة، مؤسسات سليمة; Logistic analysis, Financial ratios, Failure enterprises, Healthy enterprises. (JEL) Classification: C1, G17 ،G32 ،G33.